PENGARUH EKSTRAK DAUN TAPAK DARA (Catharantus roseus) TERHADAP KEGAGALAN SITOKINESIS SEL SPERMATOSIT PRIMER BELALANG - Kamalia Fikri (BIOEDUKASI, 2016)
Catharanthus roseus known as tapak dara generates specific bisindole alkaloids namely vinblastine and vincristine, which are potent as anticancer agents. This study is aimed to find out the effect of Catharanthus roseus leaves extract on cytokinesis failure. The treatment of concentration of Catharanthusroseus leaves extract in Carlson’s solution consisted of five concentration levels: 0.1%, 0.3%, 0.5%, 0.7% dan 0.9%. Carlson’s solution was utilized as the control. The result of this study revealed that Catharanthus roseus leaves extract has significantly effect on cytokinesis failure. Moreover, there was afailure of division. Key words: Catharanthus roseus leaves, extract, cytokinesis failure